Occupational Stress and Its Effect on Job Performance: The Moderating Role of Age, Gender, and Position Among Bank Employees in Nepal - Bhatt, Sandip; Basnet, Sandip; Karkee, Sunil (Apex Journal of Business and Management, 2026)
Nepal's banking sector has expanded rapidly, yet rising occupational stress threatens employee performance amid growing workloads and role pressures. This study investigates occupational stress's direct impact on job performance and the moderating roles of age, gender, and job position among commercial bank employees. A convenience sample of 190 Kathmandu-based bank employees completed surveys. Descriptive, correlation, causal-comparative, and moderation analyses examined stress sources (workload, role ambiguity, work environment) and their performance linkages, testing demographic moderators. Findings confirm significant negative relationships between job performance and workload, responsibility ambiguity, and adverse work environments. Moderation analysis reveals age and job position significantly alter the stress-performance relationship—younger and lower-position employees show heightened vulnerability—while gender exerts no differential effect. Moderate stress may enhance output relative to baselines, but excessive levels impair performance, particularly among junior staff. Bank managers should prioritize stress mitigation for younger, lower-echelon employees through targeted programs addressing workload distribution and role clarity to optimize sector productivity.